Analysis and improvement of two-mass vibrating tubular conveyers with two-cycle electromagnetic drive - Shenbor, Vladyslav; Koruniak, Petro; Korendiy, Vitaliy; Brusentsov, Volodymyr; Brusentsova, Marta (Publishing House of Lviv Polytechnic National University, 2016)
The analysis of structure diagrams of the two-mass tubular conveyer with two-cycle electromagnetic drive is carried out in the article. Two methods of designing of the elastic system are considered; calculation formulas for elastic system computation are deduced according to different requirements for the operating parameters of conveyers; the comparative analysis of two types of elastic systems is conducted. The recommendations for designing the lengthy tubular vibrating conveyers are presented. According to the considered structural diagrams of the elastic system the models of the lengthy vibrating conveyers with the transporting distances l =1,5...4 m are developed. On the basis of these models the lengthy vibrotransporting systems with the transporting distance l = 5...30 m were developed, manufactured and applied in industry. The considered systems ensures the transportation of loose materials (porcelain composition, sand etc.) with maximal speeds up to 800 mm/sec and productivities (for tubes with internal diameter D =100 mm) up to 30 tons per hour for. It is reasonable to use both considered schemes of elastic systems for development of vibrating tubular conveyers with electromagnetic drive. The conveyers may be designed in two modifications: overhead and supporting. The obtained dependencies allow optimization of the structure and considering the important technical parameters of conveyers (maximal permissible oscillations amplitude, springs stresses, productivity etc.) in the design phase.